Regulatory Role of N6‐methyladenosine (m6A) Methylation in RNA Processing and Human Diseases. Issue 9 (15th May 2017) - Wei, Wenqiang; Ji, Xinying; Guo, Xiangqian; Ji, Shaoping
ABSTRACT: N 6 ‐methyladenosine (m 6 A) modification is an abundant and conservative RNA modification in bacterial and eukaryotic cells. m 6 A modification mainly occurs in the 3′ untranslated regions (UTRs) and near the stop codons of mRNA. Diverse strategies have been developed for identifying m 6 A sites in single nucleotide resolution. Dynamic regulation of m 6 A is found in metabolism, embryogenesis, and developmental processes, indicating a possible epigenetic regulation role along RNA processing and exerting biological functions. It has been known that m 6 A editing involves in nuclear RNA export, mRNA degradation, protein translation, and RNA splicing. Deficiency of m 6 A modification will lead to kinds of diseases, such as obesity, cancer, type 2 diabetes mellitus (T2DM), infertility, and developmental arrest. Some specific inhibitors against methyltransferase and demethylase have been developed to selectively regulate m 6 A modification, which may be advantageous for treatment of m 6 A related diseases. J. Cell. Biochem. 118: 2534–2543, 2017. © 2017 Wiley Periodicals, Inc. Abstract : m 6 A is a conservative RNA modification in bacterial and eukaryotic cells. m 6 A is dynamically modulated in metabolism, embryogenesis, and developmental processes. m 6 A editing may be involved in mRNA degradation, protein translation, and RNA splicing. Deficiency of m 6 A could be involved in diverse diseases in human beings.